(untitled) (LEARNing Landscapes, 2009)
I have come to believe that most students who have read and studied poetry in school and college do not go on to read and enjoy poetry in their adult lives because they do not expect to understand a poem of any complexity on their own. Unfortunately, years of conditioning into such dependence have also victimized teachers into functioning as guardians of the poem’s meaning. In an attempt to find out what students could realize from a poem without teacher direction, I discovered in studies at various levels of schooling that students working in small groups without any expectation that the teacher held and would provide "the one right meaning," generated rich and powerful readings of challenging poems far beyond any understanding that the teacher could have mediated with questions.